A principled approach to designing computational thinking concepts and practices assessments for upper elementary grades. Issue 2 (3rd April 2021) - Basu, Satabdi; Rutstein, Daisy W.; Xu, Yuning; Wang, Haiwen; Shear, Linda
ABSTRACT: Background and Context : In today's increasingly digital world, it is critical that all students learn to think computationally from an early age. Assessments of Computational Thinking (CT) are essential for capturing information about student learning and challenges. When programming is used as a vehicle to foster CT skills, assessment of CT skills needs to measure understanding of programming concepts alongside general problem-solving practices applicable in contexts beyond programming. Objective : In this paper, we discuss the development of and results from separate validated assessments of programming concepts and generic CT practices for 4 th -6 th grade students. Method : An Evidence-Centered Design approach was used for the development and validation of the assessments, that were used with 15, 000 upper elementary students in Hong Kong. Findings : Results from assessment implementation indicate that the assessments worked as designed and reveal student challenges with CT concepts and practices. Implications : These results point to the utility of our assessment as a curricular tool and the need for emphasizing certain CT concepts and practices in future curricular initiatives and teacher professional development.